Traditional and asynchronous computer-assisted instruction in a community college remedial mathematics course: a mixed methods study of student success and perceptions - Hogan, Stacey L., author; Timpson, William, advisor; Chappell, Kelly, committee member; Ginsberg, Richard, committee member; Gloeckner, Gene, committee member (Colorado State University. Libraries, 2005)
The purpose of this study was to increase understanding about the impact of instructional delivery method on students' final grades in a community college remedial mathematics course. The study specifically addressed the effectiveness of using Interactive Mathematics software developed by Academic Systems Corporation. The study included two parts, which were conducted simultaneously. The first part was quantitative and the second part was qualitative. In the first part of the study, the investigator used archived student data to analyze the relationship between instructional delivery method (traditional instruction vs. asynchronous computer-assisted instruction [CAI]), students' gender, students' age, and students' final course grades in Survey of Algebra and in a subsequent, college-level mathematics course (College Algebra). Data were analyzed from 1,720 students who enrolled in Survey of Algebra from 2002 to 2004. Results indicated that students who used traditional instruction had higher grades than students who used CAI; females had higher grades than males, regardless of type of instruction; and non-traditional age students had higher grades than traditional age students, regardless of type of instruction. In most cases, the differences were statistically significant when analyzed using t tests. Effect sizes ranged from small to medium-large. Results of an ANOVA indicated that although the main effects were significant and large, there were no significant interactions between the independent variables. The second part of the study was a qualitative exploration of students' experiences and perceptions using asynchronous CAI. The investigator conducted 12 one-on-one interviews with students and used a systematic, multi-level coding process for analyzing and interpreting data from the interviews. Students' experiences in and perceptions about taking Survey of Algebra using computerized instruction seemed to be based on the degree to which external variables (i.e., the structure and format of the course) were or were not compatible with students' personal characteristics, learning preferences, prior knowledge of the content, and aptitude for mathematics. Three major themes related to CAI were salient across all interviews - convenience, individualization, and support - although some students commented favorably and others commented unfavorably about those aspects of using CAI. Results of this study suggest that method of instruction can be a factor in student success in remedial mathematics courses. Traditional instruction was found through quantitative analysis to be the more effective method of instruction. However, qualitative analysis showed that some students had a strong preference for CAI and were successful in Survey of Algebra using CAI. There appear to be advantages to both methods of instruction. The overall implication stemming from this study is that traditional instruction should not be eliminated and nor should CAI. Instead, the participating institution should continue to offer remedial mathematics courses in a variety of instructional formats, perhaps guiding each student toward a particular method of instruction based upon his/her unique mix of personal and motivational qualities. Because this was a study of a single institution, similar studies should be conducted before results can be generalized to a larger population of developmental mathematics students.
Keywords: community colleges; mathematics education; educational technology